Entrepreneur students earn No. 1 national acclaim - Uribes, Tom::::::::: (2013)
Fresno State's Collegiate Entrepreneurs Organization (CEO) won the Campus E-Diffusion Award at the organization's national conference in Chicago, besting 250 university teams for first place.